Early Life Experiences Moderate the Relationship Between Genetic Risk of Autism and Current and Lifetime Mental Health - Shin, Su Hyun; Wright, Cheryl; Johnston, Susan (Frontiers in Psychiatry, 2021)
Although individuals with autism are at greater risk of mental health challenges than others, we know little about the relationship between the mental health of older adults (50+) and autism because they are less likely to be diagnosed. Identifying the risk and protective factors that contribute to mental health can increase educational awareness, inform clinical practice, and provide information to help diagnose and treat older adults with autism. This study used longitudinal panel data of the 2008-2016 waves of the Health and Retirement Study. It estimated individual random-effect models by interacting a genetic propensity toward autism and early life experiences to test whether the latter has a moderating effect on the relationships between genetics and the Center for Epidemiologic Studies Depression (CES-D) score, self-reported depression, and history of psychiatric problems. Results suggest that individuals with a higher genetic propensity for autism are less likely to develop psychiatric problems if they report a positive maternal relationship early in life. Further, a combined effect of police encounters early in life and genetic risk for autism is associated with higher CES-D scores, increased odds of self-reported depression, and a history of psychiatric problems. Clinical applications of these findings include the need to establish and support high-quality relationships by addressing both child and caregiver needs. Further, these findings support the need to design and implement proactive interventions to teach police and autistic individuals how to successfully navigate these encounters.